Poeta narysowany – o puszkinowskiej trylogii Andrieja Chrżanowskiego - Czaja, Justyna (Przestrzenie Teorii, 2019)
Czaja Justyna, Poeta narysowany – o puszkinowskiej trylogii Andrieja Chrżanowskiego [A Drawn Poet – about Andrei Khrzhanovsky’s A Pushkin Trilogy]. „Przestrzenie Teorii” 32. Poznań 2019, Adam Mickiewicz University Press, pp. 357–370. ISSN 1644-6763. DOI 10.14746/ pt.2019.32.19. The subject of the article is an animated film A Pushkin Trilogy directed by Andrei Khrzhanovsky, dedicated to Alexander Pushkin. It comprises the films: Ya k vam lechu vospominanem, I s vami snova ya and Osen. The article attempts to answer the question about the reasons for the director’s interest in this outstanding writer and his work. It also shows the evolution of the ‘Pushkin theme’ in Khrzhanovsky’s work, changes in the content and formalism, and artistic research that led to the creation of the original animated trilogy. The poetics of the work are analyzed, in which the director looks at the work of the Russian writer through the prism of his manuscripts and sketches, while at the same time expanding the formula of the biographical film.